Kemampuan Guru Mata Pelajaran Agama Hindu dalam Menjalankan Tugas Pembelajaran di Sekolah Dasar (Studi Kasus Sekolah Dasar Negeri di Kabupaten Karanganyar) - I Nyoman Suendi (Jayapangus Press, 2019)
This study aims to find out about the ability of Hindus subject teachers in compiling syllabus subjects in Elementary Schools in Karanganyar District, implementing Hinduism subject learning in Karanganyar Regency, students' responses in participating in Hinduism subject learning. This study uses descriptive qualitative research method with a single embedded case study strategy because this study is directed at a characteristic, namely the ability of Hinduism subject teachers in carrying out learning tasks. The data source consisted of informants who included Hindu religious teachers, principals, deputy principals for curriculum affairs, library officers and students in grades V and VI, learning activities, facilities and infrastructure, locations, namely the condition of the school environment, especially classrooms, archives and documents includes learning tools, syllabus, and student assignments. Data was collected by in-depth interviews, observation and document analysis. The analysis technique uses an interactive analysis model, namely the interaction between data collection and three components of analysis, namely: data presentation, data reduction, and verification / conclusion in a cycle. The results of the study showed that the majority of Hindu subject teachers in Elementary Schools in Karanganyar District had been able to compile the syllabus well in accordance with the characteristics of the Karanganyar Elementary School which must be made as a direction for teachers in teaching which contained material descriptions, learning objectives , time allocation, methods, media, and evaluation techniques in the form of formative tests, final examination tests. There are a small number of Hindu subject teachers who do not compile syllabi. The material only depends on the syllabus of the results of the Teacher Working Group (KKG). In addition, optimal cooperation has not been established between teachers, principals, school committees and education councils, in discussing the curriculum including in formulating syllabus so that it influences the less than optimal performance of teachers in carrying out assignments in Karanganyar Elementary School, in the process of learning religious subjects Hindus in the class, Hinduism subject teachers convey constraints, including frequently changing curriculum factors, time allocation, infrastructure, and student factors. These obstacles are crucial in the learning process of Hinduism. In overcoming these obstacles Hinduism subject teachers always prepare themselves carefully and try to look attractive with the media, methods, and evaluations that are used even though it is still conventional means to use the lecture method due to limited time with balanced material, the teacher only conveys the outline only, the response of students to Hindu religious subjects is negative and deviates from the provisions, the 2013 curriculum objectives. This is indicated by: indifferent to Hinduism subject teachers, responses in the passive learning process, only as loyal listeners, without critical thinking , rarely ask the teacher, there is an idol in learning Hinduism subjects, the means in the form of Hinduism subject books that students have are very minimal, students only have limited textbooks that are borrowed from the library, lack of students' understanding of the meaning or value that contained in learning of Hinduism.